2015
DOI: 10.1080/09205063.2015.1066109
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of polyacrylamide/silk fibroin hydrogels for peripheral nerve regeneration

Abstract: Various hydrogels have been used for repairing peripheral nerve injury; however, the silk fibroin (SF)-based hydrogels in peripheral nerve regeneration are still rarely reported. In this study, the SF/pAM hydrogels with different SF concentrations and ethanol treatment time were developed by solution blending and in situ radical polymerization. The physiochemical properties of composite hydrogels were measured, the cytotoxicity of hydrogels was evaluated by L929 fibroblasts, and the effect on peripheral nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…The novelty of this study comes from the fact that this is one of the few instances in which a self-healing hydrogel, which is expected to gain major popularity in coming years, has been shown to be effective in vivo for nerve regeneration applications. Silk fibroin-based hydrogels are unfortunately still rarely used for nerve regeneration applications, despite the fact that they have shown little to no cytotoxicity and allow for significant nerve regeneration when used with Schwann cell cultures in vitro [164]. Much of the success of the hydrogel scaffold has to do with stiffness.…”
Section: Applicationsmentioning
confidence: 99%
“…The novelty of this study comes from the fact that this is one of the few instances in which a self-healing hydrogel, which is expected to gain major popularity in coming years, has been shown to be effective in vivo for nerve regeneration applications. Silk fibroin-based hydrogels are unfortunately still rarely used for nerve regeneration applications, despite the fact that they have shown little to no cytotoxicity and allow for significant nerve regeneration when used with Schwann cell cultures in vitro [164]. Much of the success of the hydrogel scaffold has to do with stiffness.…”
Section: Applicationsmentioning
confidence: 99%
“…Many natural and synthetic materials possess some of these ideal properties, however, none are perfect. Therefore, biomaterial composites of both synthetic and natural materials provides an ideal solution by combining the optimal properties of each component into one system [ 13 , [18] , [19] , [20] ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrogels have been widely used in tissue engineering and nerve regeneration due to their good biocompatibility, water retention and drug‐delivery properties . Ortuno‐Lizaran et al fabricated biodegradable hyaluronic acid hydrogel conduit by chemical cross‐linking, and found that Schwann cells could grow well in the conduit lumen.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrogels have been widely used in tissue engineering and nerve regeneration due to their good biocompatibility, water retention and drug-delivery properties. [18][19][20][21][22][23][24] Ortuno-Lizaran et al 25 fabricated biodegradable hyaluronic acid hydrogel conduit by chemical cross-linking, and found that Schwann cells could grow well in the conduit lumen. Gonzalez-Perez et al 26 prepared collagen hydrogel-filled chitosan conduits containing extracellular matrix, the conduit could promote the repair of peripheral nerve injury to a certain extent, which may be used as a potential candidate in the repair of peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%